Karyotype analysis of some Lathyrus L. species (Fabaceae) from the Thrace region (Turkey-in-Europe) - (:unkn) unknown (FIRENZE UNIV PRESS, 2008)
A total of 16 wild species of the genus Lathyrus grown wildly in the region of Thrace (Turkey) were collected, identified and examined for karyotype analysis. The species diversity found in this work includes approximately one fourth of all the Lathyrus species in Turkey. Collected specimen were identified as L. niger (L.)Bernh. subsp. niger, L. palustris L. subsp. palustris, L. laxiflorus (Desf.) O.Kuntze subsp. laxiflorus, L. tuberosus L., L. undulatus Boiss., L. sylvestris L., L. sphaericus Retz., L. setifolius L., L. annuus L., L gorgoni Parl. var. pilosus C.C.Townsend, L. cicera L., L. hirsutus L., L. clymenum L., L. ochrus (L.)DC., L. nissolia L., L. aphaca L. var. aphaca. The chromosome number of A studied taxa except L. palustris L. subsp. palustris (2n=42) was determined 2n=14, x=7. Studies of karyotype analyses among some species of Lathyrus including L. niger subsp. niger, L. palustris subsp. palustris, L. tuberosus, L. undulatus (endemic for Turkey) L. gorgoni var. pilosus, L. clymenum L., L. ochrus (L.)DC and L. aphaca L. var. aphaca have not been investigated in Turkey. Hence, this data is also the first report on the karyotype analysis of those six species grown in the Thrace region.
Keywords: Lathyrus; karyotype analysis; Turkey-in-Europe; CYTOTAXONOMIC INVESTIGATIONS